Graft-versus-host disease in a child with neuroblastoma after autologous stem cell transplantation - Yaman, Yöntem; Baysoy, Gökhan; Keleşoğlu, Emre; Özdilli, Kürşat; Çakır, Aslı; Genç, Dildar Bahar; Elli, Murat; Anak, Sema (Contemporary Oncology/Współczesna Onkologia, 2019)
In the pediatric population, hematopoietic stem cell transplantation (HSCT) is used to treat a wide variety of diseases, both malignant and nonmalignant. For many of these diseases, HSCT is a well-established treatment. Acute graft-versus-host disease (GVHD) continues to be a leading cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Graft versus host disease is a common complication of allo-SCT which is induced by donor T cell recognition of recipient alloantigens. The occurrence of autologous GVHD suggests that inappropriate recognition of host self-antigens may occur. GVHD in patients who received autologous HSCT is extremely rare compared to patients who received allogeneic HSCT. We present the case of a 4-year-old girl with metastatic neuroblastoma who spontaneously developed autologous GVHD after autologous HSCT.